Strain Variation in Adenovirus Serotypes 4 and 7a Causing Acute Respiratory Disease - Crawford-Miksza, Leta K. (American Society for Microbiology, 1999)
In order to determine the suitability of vaccine strains established in the 1960s for a new vaccine, a comprehensive study of strain variation of adenovirus serotype 4 (AV 4) and AV 7 was undertaken. A 1,500-bp region of the hexon gene containing the AV neutralization epitopes from prototype, vaccine, and community-acquired strains and from wild-type strains from military personnel that cause acute respiratory disease (ARD) was sequenced and analyzed. The whole hexon gene from prototype strains, vaccine strains, and selected isolates was sequenced. AV 7 and AV 7a were found to have distinct genotypes, and all vaccine and wild-type strains recovered from 1963 to 1997 had the AV 7a genotype. There was no significant strain variation in the neutralization epitopes of the AV 7a genotype over a 42-year period. The evolution of AV 4 was more complex, with continuous genetic drift punctuated by replacement with a new strain. The current strain of AV 4, which has been in circulation since 1995, is significantly different from the AV 4 prototype and the vaccine strains. Genetic differences were confirmed to be antigenic differences by neutralization tests, which define the new strain as an AV 4 variant. A type-specific PCR for AV 4, AV 7/7a, and AV 21 was developed, and this PCR facilitated the rapid identification of isolates from outbreaks of ARD.